Pengaruh Minat Terhadap Hasil Belajar Siswa Menggunakan Metode TAI (Team Assisted Individualization) Pada Materi Dunia Tumbuhan - R. Makin, Florian Mayesti Prima (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
The objective of this study was to investigate the effect of learning interest on the students’ learning achievement by using the TAI (Team Assisted Individualization) method on the material of world of plants. The research was designed with Classroom Action Research (CAR) Khemmis and Mc. Taggart. The subjects of research were the students of class X1 of Pangudi Luhur High School Yogyakarta in the 2012-2013 academic years with 35 total numbers of students. The instruments of data collection are tests and non-tests. The percentage of students' interest reached 83.34% and the average of the increase of the students’ learning achievement in the cognitive aspect from cycle I to cycle II was 40.3 to 57.63. The finding showed that the learning interest affected the students’ learning achievement in the cognitive aspect, when the students’ interest in learning is high, the learning achievement will increase.